2004
DOI: 10.1196/annals.1306.025
|View full text |Cite
|
Sign up to set email alerts
|

Ironing Iron Out in Parkinson's Disease and Other Neurodegenerative Diseases with Iron Chelators: A Lesson from 6‐Hydroxydopamine and Iron Chelators, Desferal and VK‐28

Abstract: In Parkinson's disease (PD) and its neurotoxin-induced models, 6-hydroxydopamine (6-OHDA) and N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), significant accumulation of iron occurs in the substantia nigra pars compacta. The iron is thought to be in a labile pool, unbound to ferritin, and is thought to have a pivotal role to induce oxidative stress-dependent neurodegeneration of dopamine neurons via Fenton chemistry. The consequence of this is its interaction with H(2)O(2) to generate the most reactive ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(131 citation statements)
references
References 86 publications
3
124
1
2
Order By: Relevance
“…2B), CQ administration alone and in the presence of MPTP elicited stabilization of cytosolic HIF-1␣ (Fig. 6B) suggesting that activation of the HIF pathway by CQ could in part underlie the protection against DAergic cell loss observed in various studies utilizing iron chelation therapy in MPTP PD models (13,32).…”
Section: Short-term Pre-treatment With the Bioavailable Iron Chelatormentioning
confidence: 99%
“…2B), CQ administration alone and in the presence of MPTP elicited stabilization of cytosolic HIF-1␣ (Fig. 6B) suggesting that activation of the HIF pathway by CQ could in part underlie the protection against DAergic cell loss observed in various studies utilizing iron chelation therapy in MPTP PD models (13,32).…”
Section: Short-term Pre-treatment With the Bioavailable Iron Chelatormentioning
confidence: 99%
“…One of the well-recognized pathways responsible for generation of oxidative radicals is mitochondrial toxicity induced by accumulation of MPP + in the inner mitochondrial membrane, and the subsequent disruption of complex I in the electron transport chain (Cassarino et al, 1999;Fiskum et al, 2003;Kalivendi et al, 2003). Studies have also shown auto-oxidation of the neurotransmitter dopamine (Obata, 2002;Sidhu et al, 2004) or the interaction of MPP + with iron stores within the pigmented substantia nigra cells as possible sources of oxidative stress (Andersen, 2004;Mandel et al, 2004;Youdim et al, 2004;Mancuso et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oxidative stress is involved as one of the causes in neurodegenerative disorders like AD and PKD (Gotz et al, 1990;Riederer et al, 1989;Perry et al, 2002) and age associated behaviour deficits (Shukitt-Hale, 1999). Apart from oxidative stress, inflammatory changes and iron accumulation (Gerlach et al, 2003;Youdim et al, 2004) have been suggested and reported to be involved in neurodegenerative diseases. Iron accumulation occurs in specific areas of the brain where degeneration occurs, in both PKD and AD (Riederer et al, 1989).…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%